Strategi Penempatan Pegawai Berdasarkan Sistem Merit pada Direktorat Pembinaan dan Pengawasan Tenaga Kesehatan Kementerian Kesehatan - Yani, Mohammad; Sutrisno, Edy; Rahayu, Neneng Sri (Universitas Batanghari Jambi, 2024)
Human Resources have an important role and become the key to success in carrying out activities to achieve the vision and mission of the organization. HR problems in Government Agencies are not only in HR Professionalism. In addition, organizational changes need to be made to face national development and global competition. In organizational changes, employee placement based on qualifications, competencies and performance needs to be done properly so that employee professionalism is maintained. The purpose of this study is to find employee placement strategies based on the merit system at the Directorate of Health Worker Development and Supervision to run optimally. This study used a descriptive method of qualitative approach with data collection using observation, interviews, and documentation. The number of informants in this study was 5 people with data analysis techniques using data reduction, data presentation, and conclusions. The results of this study state that the placement of employees based on the merit system has not run optimally, there are still problems including there are employees who have not been improved in competence, performance appraisals have not been consistently carried out based on organizational and employee performance targets, and have not carried out competency development mapping based on performance and competency gaps. The age factor is still a consideration in employee placement so that the application in the concept of performance achievement has not been carried out optimally. The resulting strategy is by mapping and improving competency development based on competency and performance gaps, conducting objective and measurable performance appraisals based on organizational and employee performance goals, changing organizational culture and implementing talent management in accordance with applicable regulations.